Apparent phototaxis enabled by Brownian motion. Issue 47 (28th October 2020) - Niese, Lukas; Wang, Linlin; Das, Sayan; Simmchen, Juliane
Abstract : To improve the understanding of phototaxis, we investigate the origin of our photocatalytic particles' peculiar scotophobicity (fear of darkness). Abstract : Biomimetic behaviour in artificially created active matter that allows deterministic and controlled motility has become of growing interest in recent years. It is well known that phototrophic bacteria optimize their position with respect to light by phototaxis. Here, we describe how our fully artificial, magnetic and photocatalytic microswimmers undergo a specific type of behaviour that strongly resembles phototaxis: when crossing an illuminated stripe the particles repeatedly turn back towards the light once they reach the dark region, without any obvious reason for the particles to do so. In order to understand the origin of this behaviour we analyze different influences and elucidate through experiments and theoretical considerations that this behavior arises from a combination of orientational stabilization through activity and destabilizing Brownian motion. This interplay shows beautifully how simple physical effects can combine into complex behaviours.